2005
DOI: 10.1002/per.536
|View full text |Cite
|
Sign up to set email alerts
|

Parent–offspring similarity in personality and adolescents' problem behaviour

Abstract: Similarity in personality between adolescents and their parents may have considerable implications for adolescent well-being. We studied how the similarity in personality between 288 adolescents and their parents is linked to adolescent problem behaviour, and whether this link is mediated by warmth and control in the parent-child relationship and moderated by the personality type of the adolescent. Similarity in personality between adolescents and their parents was negatively related to internalizing and exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 59 publications
4
28
3
Order By: Relevance
“…Parents reported on physical resemblance on the item: ''I think my child looks like me''. Personality similarity was calculated using Q-correlations based on a 30-item version of the Big Five questionnaire (Goldberg, 1992) filled out by the parents about themselves and their child (for details see van Tuijl et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents reported on physical resemblance on the item: ''I think my child looks like me''. Personality similarity was calculated using Q-correlations based on a 30-item version of the Big Five questionnaire (Goldberg, 1992) filled out by the parents about themselves and their child (for details see van Tuijl et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore it is not possible to determine whether it is physical resemblance, or personality similarity, or both, that contributes to the link with parental investment. The only study examining personality similarity in relation to parental investment found that personality similarity was linked to the quality of the parent-adolescent relationship for mothers, but not for fathers (van Tuijl, Branje, Dubas, Vermulst, & van Aken, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Previous factor analysis of Relational Support Inventory responses carried out within the same data set (van Tuijl, Branje, Dubas, Vermulst, & van Aken, 2005) resulted in two clearly interpretable factors that are consistent with previous research (Maccoby & Martin, 1983) The Big Five traits of Extraversion, Agreeableness, Conscientiousness, Emotional Stability, and Openness to Experience were assessed with a Dutch adaptation (Gerris et al, 1998) of 30 adjective Big Five personality markers selected from Goldberg (1992). Sample items include "talkative" and "reserved" (reverse coded) for Extraversion; "sympathetic" and "kind" for Agreaableness; "careful" and "organized" for Conscientiousness; "anxious" (reverse coded) and "nervous" (reverse coded) for Emotional Stability; and "imaginative" and "creative" for Openness to Experience.…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, a good fit is typically seen as the mix of similar characteristics in parents and children resulting in compatibility and positive adjustment. For example, similarity in parent and adolescent personalities, measured as Big 5 factors (Goldberg, 1992), has been associated with fewer adolescent internalizing and externalizing problems (Van Tuijl, Branje, Dubas, Vermulst, & Van Aken, 2005). A poor fit is sometimes defined as the mix of similar risk-inducing characteristics such as a propensity for conflictual interactions (Burt, Krueger, McGue, & Iacono, 2003) or high novelty seeking (Rettew, Stanger, McKee, Doyle, & Hudziak, 2006).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%